Normal numbers and the Borel hierarchy - Becher, Veronica Andrea (2014)
We show that the set of absolutely normal numbers is Π03-complete in the Borel hierarchy of subsets of real numbers. Similarly, the set of absolutely normal numbers is Π03-complete in the effective Borel hierarchy.